2003
DOI: 10.1074/jbc.m304333200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Association of the Cytoplasmic Tail of MUC1 and β-Catenin

Abstract: MUC1, an integral membrane mucin associated with the metastatic phenotype, is overexpressed by most human carcinoma cells. The MUC1 cytoplasmic tail (CT) is postulated to function in morphogenetic signal transduction via interactions with Grb2/Sos, c-Src, and ␤-catenin. We investigated intracellular trafficking of the MUC1 CT, using epitope-tagged constructs that were overexpressed in human pancreatic cancer cell lines S2-013 and Panc-1. The MUC1 CT was detected at the inner cell surface, in the cytosol, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
166
2
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(184 citation statements)
references
References 66 publications
12
166
2
4
Order By: Relevance
“…For instance, a fragment of the MUC1 cytoplasmic tail is cleaved and transported into the nucleus in association with b-catenin, affecting its function as a co-activator for TCF/LEF1 (Wen et al, 2003). Both MUC1 and MUC4 also associate with ErbB tyrosine kinase receptors on the cell membrane and enhance the downstream mitogen-activated protein Figure 6 Immunohistochemical analysis of GLI1, MUC5AC, E-cadherin and b-catenin in PanIN and PDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a fragment of the MUC1 cytoplasmic tail is cleaved and transported into the nucleus in association with b-catenin, affecting its function as a co-activator for TCF/LEF1 (Wen et al, 2003). Both MUC1 and MUC4 also associate with ErbB tyrosine kinase receptors on the cell membrane and enhance the downstream mitogen-activated protein Figure 6 Immunohistochemical analysis of GLI1, MUC5AC, E-cadherin and b-catenin in PanIN and PDA.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the expressions of MUC1, MUC2 and MUC5AC were statistically associated with a shorter survival time for pancreatic cancer patients in the United States (Takikita et al, 2009), suggesting that mucin functions not only to protect the normal epithelial surface from harsh environments but also to regulate cancer cell properties. Indeed, membrane-associated mucins were recently shown to play a crucial role in signal transduction (Schroeder et al, 2001;Jepson et al, 2002;Wen et al, 2003;Hollingsworth and Swanson, 2004;Bafna et al, 2010). However, the role for gel-forming mucins in cancer cells is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…As MUC1 CT and galectin-3 in the nucleus promote cyclin-D1 expression through the accumulation and/ or stabilization of nuclear b-catenin, respectively (Wen et al, 2003;Song et al, 2009), we studied the levels of cyclin D1 in total cell lysates before and after a 10-min EGF treatment (Figure 4c). Our results show that Sc cells expressed higher levels of cyclin D1 than Sh1 cells in absence or in presence of EGF.…”
Section: Galectin-3 Promotes Muc1 and Egfr Endocytosis J Merlin Et Almentioning
confidence: 99%
“…For example, epidermal growth factor receptor (EGFR) phosphorylates this peptide motif and promotes the binding of MUC1 CT to c-Src and b catenin (Li et al, 2001). MUC1 CT also co-localized with b-catenin in the nucleus thus suggesting that it could be cleaved/ released from the membrane and traffic from the membrane to the cytoplasm and nucleus (Wen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…3B), indicating that this response is not cell type specific. Other studies have shown that MUC1-C, but not MUC1-N, is trafficked to the nucleus (8,9,11,44,45). Analysis of purified nuclei from ZR-75-1 cells showed that FGF1 increases MUC1-C levels (Fig.…”
Section: Fgf1 Targets Muc1 To the Cytosol And Nucleusmentioning
confidence: 99%